#Gymlad - young boys learning processes and health-related social media. Issue 1 (1st January 2020) - Goodyear, Victoria; Quennerstedt, Mikael
ABSTRACT: Recent systematic reviews identify that the factors mediating and/or moderating the relationship between social media and health outcomes are sparse. There have also been few attempts to analyse gender specific uses of social media. This paper investigated young boys health-related learning in relation to social media. Data were generated from class activities and interviews and from a large data set that included 1346 young people. The approach to the empirical data adopted was Practical Epistemology Analysis (PEA). The findings reveal two main purposes of young boys engagement with social media: (i) communicating with friends, and (ii) accessing health-related information. Irony and humour were central learning mechanisms used by young boys to participate within health-related social media, and in a way that enabled them to engage with, uphold, and handle health discourses associated with masculinity – such as being ripped – without fear of 'literal' peer ridicule and within a context of acceptable 'banter'. There was evidence that young people were critical users and generators of social media, who were clearly thinking through what they see, do, and use online. Hence, this paper provides a fresh evidence-based perspective on the potentially positive role of social media as a health-related learning resource. PEA is illustrated as a new methodological approach for investigating learning in the context of social media. The evidence generated can be used to inform future evaluations of social media use, the design of educative support for young people, and guidance and training for key stakeholders.